Byron and the Forms of Thought - Howe, Anthony (Liverpool English Texts and Studies, 2013)
Byron and the Forms of Thought is a major new study of Byron as a poet and thinker. While informed by recent work on Byron's philosophical contexts, the book questions attempts to describe Byron as a philosopher of a particular kind. It approaches Byron, rather, as a writer fascinated by the different ways of thinking philosophy and poetry are taken to represent.After an Introduction that explores Byron's reception as a thinker, the book moves to a new reading of Byron's scepticism, arguing for a close proximity, in Byron's thought, between epistemology and poetics. This is explored through readings of Byron's efforts both as a philosophical poet and writer of critical prose. The conclusions reached form the basis of an extended reading of Don Juan as a critical narrative that investigates connections between visionary and political consciousness. What emerges is a deeply thoughtful poet intrigued and exercised by the possibilities of literary form.